2016
DOI: 10.18632/oncotarget.8532
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effects of curcumin on lung cancer through the inhibition of EZH2 and NOTCH1

Abstract: Curcumin is potentially therapeutic for malignant diseases. The mechanisms of this effect might involve a combination of antioxidant, immunomodulatory, proapoptotic, and antiangiogenic activities. However, the exact mechanisms are not fully understood. In the present study, we provided evidences that curcumin suppressed the expression of enhancer of zeste homolog 2 (EZH2) in lung cancer cells both transcriptionally and post-transcriptionally. Curcumin inhibited the expression of EZH2 through microRNA (miR)-let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 54 publications
(51 reference statements)
0
50
0
Order By: Relevance
“…The repression of EZH2 has been proved to be a possible therapeutic method for the treatment of malignant cancers [Bauge et al, ; Fillmore et al, ]. In 2016, Guo‐Qing et al suggested that curcumin can inhibit lung cancer by silencing gene EZH2 [Wu et al, ]. Moreover, recently the targeting relationship between miR‐101 and EZH2 has also been spotted.…”
mentioning
confidence: 99%
“…The repression of EZH2 has been proved to be a possible therapeutic method for the treatment of malignant cancers [Bauge et al, ; Fillmore et al, ]. In 2016, Guo‐Qing et al suggested that curcumin can inhibit lung cancer by silencing gene EZH2 [Wu et al, ]. Moreover, recently the targeting relationship between miR‐101 and EZH2 has also been spotted.…”
mentioning
confidence: 99%
“…As a natural derivative of Curcuma Longa, CL extract demonstrates strong cancer chemopreventive properties through the activation of apoptosis or inhibition of the cell cycle (23,24). Numerous studies have revealed that CL extract causes anti-cancer activities in many types of malignancies either as single agent or in combination with other drugs (25)(26)(27)(28)(29)(30). In this study, we aimed at examining the anti-cancer activity of CL extract and its synergistic effect in combination with prednisolone on acute lymphoblastic leukemia Nalm-6 and REH cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, zinc oxide nanoparticles can kill breast cancer cells and liver cells directly . Extracted from the rhizome of Curcuma longa as a phenolic pigment, curcumin has shown many attractive biomedical functions, including anti‐inflammatory, anti‐oxidant, and anti‐cancer effects . It can induce tumor cell cycle blockage and apoptotic cell death by downregulating oncogene expression and upregulating anti‐oncogene expression, interfering with p53‐related pathways and blocking nuclear factor (NF)‐κB activation .…”
Section: Direct Killing Effectmentioning
confidence: 99%
“…[24][25][26] Extracted from the rhizome of Curcuma longa as a phenolic pigment, curcumin has shown many attractive biomedical functions, including antiinflammatory, anti-oxidant, and anti-cancer effects. 27 It can induce tumor cell cycle blockage and apoptotic cell death by downregulating oncogene expression and upregulating antioncogene expression, interfering with p53-related pathways and blocking nuclear factor (NF)-jB activation. 28,29 Arunraj et al synthesized curcumin nanospheres that showed good skin permeation and retention and could reduce melanoma growth by inhibiting glutathione S-transferase activity and COX-1/COX-2 enzymes, inducing apoptosis through the Fas receptor/caspase-8 pathway and down-regulating NF-jB signaling both in vitro and in vivo.…”
mentioning
confidence: 99%